Experimental and numerical study of the fuel effect on flame propagation in long open tubes. (February 2023) - Lecocq, Guillaume; Daubech, Jérôme; Leprette, Emmanuel
Abstract: Previous works (Daubech et al., 2019) were dedicated to gaseous flame acceleration along long pipes with a set of cases studied both experimentally and numerically. In these cases, the flammable mixture was initially quiescent and homogenously distributed. The impact of the tube diameter and material were studied trough both approaches for rather slow flames, the fuel being methane. While main features of the real flame were recovered by the chosen CFD method, some limits remained. A new experimental dataset is detailed and analyzed with a quicker flame, the fuel being hydrogen and the same experimental set-up as the one used for measuring slow flames. Thus, the fuel effect on the flame dynamics can be directly highlighted. A simple CFD approach is tested for recovering two distinct flame behaviors: a deflagration flame and another undergoing deflagration-to-detonation transition. Furthermore, the modelling results are used to propose elements of interpretation for flame acceleration. Highlights: An experimental set-up was used to study explosion in long tubes for methane-air and hydrogen-air flames. A deflagration was observed for the methane-air flame while DDT occurred for the hydrogen-air flame. A simple CFD model was used to try to recover the two distinct flames behaviors. Global quantities were extracted from CFD for explaining the physics at stake during the explosion phases for both flames.